Penguatan Nilai Produk Home Industry Menuju Kesejahteraan Masyarakat Desa Suradadi, Terara, Lombok Timur - Muhammad Zainul Majdi; Baiq Yuliana Rizkiwati; Rasyid Hardi Wirasasmita (Jurnal Pengabdian Pada Masyarakat, 2020)
STRENGTHENING HOME INDUSTRY PRODUCT VALUE TOWARDS COMMUNITY WELFARE SURADADI VILLAGE, TERARA, LOMBOK TIMUR. The results of the PKM Kemitraan 2018 in Suradadi Village, Terara District have been able to increase the value of Rinjani’s home industry products and to significantly drive the community’s economy. The various economic activities that have been successfully identified and enhanced are Business management training activities, enhancing partners’ ability to design product packaging, publishing No-PIRT and halal labels, using social media as marketing media. This activity was carried out using lecture, discussion, demonstration, direct practice, observation, and socialization methods. The lecture method is used in the process of delivering training material. The discussion method is used as a communication medium during the training. The demonstration method used in the process of providing examples in training. The direct practice method is used to apply the material that has been obtained. Observation method is carried out to observe the ability of partners during the training process and after training. The socialization was carried out to provide knowledge to issue No-PIRT and Halal MUI labels. An evaluation is conducted to determine the impact of the training that has been carried out. Outputs from this activity are: 1) increasing management knowledge, increasing knowledge in the field of design and making creative products of economic value; 2) increasing the use of the internet as a product marketing media; 3) issuance of PIRT certificate and Halal MUI label, 4) availability of face book media and as product promotion media.